Susbtituição do ligamento cruzado cranial em cães por segmento teno-ósseo homólogo conservado em glicerina a 98% e submetido a diferentes protocolos de reabilitação - Salbego, Fabiano Zanini (2006)
According to research data, today there are more than 5,000 articles published around the world dealing with the question of human and animal cruciate ligament. The surgical techniques for the reconstruction of the cranial cruciate ligament (CCL), classified as intra-articular, used homogenous, autogenous or synthetic materials with the function of anatomically substituting the original ligament and providing stabilization for the knee articulation. Most autografts possess some inconveniences as to the fragility of the donating area and the low resistance of the tissues used. On the other hand, synthetics possess biomechanical characteristics that are more adequate when compared to the biological grafts however their greatest restriction is associated with availability and high cost. Based on this fact, the present work utilized homolog implants conserved in 98% glycerin, in an attempt to produce an attainable operative technique for surgery in small animals, with a weight over 15 kg, and with a low implantation cost. The animals underwent different rehabilitation procedures, where functional clinical recuperation of the operated member and loss of muscular mass were evaluated in order to determine an appropriate physiotherapeutic procedure to be used in the rehabilitation of animals undergoing the CCL substitution. Twenty four dogs, male and female, between 2 and 8 years of age, and weighing between 15 and 30 kg were used. The animals were placed in two groups (A and B), for the evaluation of the operative technique, being that group A underwent a biopsy at 90 days and group B at 60 days. Twenty one of the dogs operated were randomly subdivided into three groups to be evaluated as to the rehabilitation process, and the remaining three dogs underwent necropsy for the histopathological exam of the bone tissues. The rehabilitation groups were divided into a control group (I), a mechanical therapy group (II), and a neuromuscular electric stimulation group (III). These groups were again subdivided according to physiotherapeutic procedures used and the period of application. The histological evaluation of the bone tendon implant at 60 and 90 days after the operation demonstrated a high degree of similarity among the groups, however, at 90 days, the presence of more uniformly organized tissues in the longitudinal direction and more mature tissues was observed. Among the rehabilitation groups, though the results were not statistically significant (p<0.005), the group that underwent neuromuscular electrical stimulation during and after the external skeletal immobilization demonstrated a better clinical response in the functional recovery of the operated member.